Sleep Restriction Increases Coordination Failure - Marco Castillo; David L. Dickinson (Institute of Labor Economics (IZA), 2020)
When group outcomes depend on minimal effort (e.g., disease containment, work teams, or indigenous hunt success), a classic coordination problem exists. Using a well-established paradigm, we examine how a common cognitive state (insufficient sleep) impacts coordination outcomes. Our data indicate that insufficient sleep increases coordination failure costs, which suggests that the sleep or, more generally, cognitive composition of a group might determine its ability to escape from a trap of costly miscoordination and wasted cooperative efforts. These findings are first evidence of the potentially large externality of a commonly experienced biological state (insufficient sleep) that has infiltrated many societies.
Keywords: C91; D91; 330; coordination games; sleep; cooperative dilemma